Impacts of Changing Sexual Behavior on Chlamydia and Gonorrhea Burden Among US High School Students, 2007 to 2017. Issue 9 (28th September 2021) - Goodreau, Steven M.; Pollock, Emily D.; Wang, Li Yan; Aslam, Maria V.; Barrios, Lisa C.; Dunville, Richard L.; Rosenthal, Elizabeth M.; Hamilton, Deven T.; Katz, David A.; Rosenberg, Eli S.
Abstract : A modeling study estimated that changes in sexual behavior among US high school students helped avert >1.3 million cases of gonorrhea and chlamydia and save nearly a billion dollars. Supplemental digital content is available in the text. Abstract : Background: Rates of adolescent sexual activity have long been declining in the United States. We sought to estimate the number of cases of gonorrhea and chlamydia averted over 1 decade associated with these declines and associated costs saved. Methods: We analyzed data from the Centers for Disease Control and Prevention's Youth Risk Behavior Survey of US high school students from 2007 to 2017 and combined it with epidemiological estimates drawn from the literature to parameterize a dynamic population transmission model. We compared transmissions from observed behavioral trends with a counterfactual scenario that assumed sexual behaviors from 2007 remained constant for 10 years. We calculated outcomes by age and for 3 racial/ethnic groups (Hispanic, non-Hispanic Black, and non-Hispanic White adolescents) who vary on underlying burden and amount of behavioral change. Results: We estimated 1, 118, 483 cases of chlamydia and 214, 762 cases of gonorrhea were averted (19.5% of burden across all ages). This yielded 474 million (2017 dollars) savings in medical costs over the decade. The largest number of averted cases (767, 543) was among Black adolescents, but the largest proportion (28.7%) was among Hispanic adolescents. Conclusions: Whatever its origins, changing sexual behavior among adolescents results in large estimated reductions in STI burden and medical costs relative to previous cohorts. Although diagnoses among adolescents have not declined at this rate, multiple explanations could make these apparently divergent trends consistent. Efforts to continue supporting effective sex education in and out of school along with STI screening for adolescents should reinforce these gains.